The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acsami.2c18053
|View full text |Cite
|
Sign up to set email alerts
|

SERS-Based Immunoassay of Myocardial Infarction Biomarkers on a Microfluidic Chip with Plasmonic Nanostripe Microcones

Abstract: We developed a new plasmonic nanostripe microcone array (PNMA) substrate-integrated microfluidic chip for the simultaneous surface-enhanced Raman scattering (SERS)-based immunoassay of the creatine kinase MB isoenzyme (CK-MB) and cardiac troponin (cTnI) cardiac markers. The conventional immunoassay usually employs a microtiter plate as the solid capture plate to form the immunocomplexes. However, the two-dimensional (2D) surface of the microtiter plate limits the capture efficiency of the target antigens due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Multiple detection platforms for cardiac enzymes are developed using a single chip with a mixture of independent CK-MB and cTnI, unlike previous complex detection platforms. [11][12][13] Multiple SERS response characteristics of CK-MB and cTnI (Figure 4C), depending on their concentrations within the clinically relevant range, were simultaneously determined for each unique non-interfering peak. Moreover, at this point, the relative concentrations were fixed at the cutoff levels of 5 ng mL −1 for CK-MB and 0.8 ng mL −1 for cTnI, [5] corresponding to the T1 value in the typical time course of CK-MB and cTnI elevations after the occurrence of an AMI event.…”
Section: Sers Immunoassaymentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple detection platforms for cardiac enzymes are developed using a single chip with a mixture of independent CK-MB and cTnI, unlike previous complex detection platforms. [11][12][13] Multiple SERS response characteristics of CK-MB and cTnI (Figure 4C), depending on their concentrations within the clinically relevant range, were simultaneously determined for each unique non-interfering peak. Moreover, at this point, the relative concentrations were fixed at the cutoff levels of 5 ng mL −1 for CK-MB and 0.8 ng mL −1 for cTnI, [5] corresponding to the T1 value in the typical time course of CK-MB and cTnI elevations after the occurrence of an AMI event.…”
Section: Sers Immunoassaymentioning
confidence: 99%
“…Acute myocardial infarction (AMI), associated with high mortality worldwide, is a type of myocardial necrosis caused by acute rapid AMI diagnosis. [7][8][9][10][11][12][13][14] Furthermore, the detection of these biomarkers can be used to trace the cause of death and disease stages in forensic science. [15][16][17] Most studies on fluorescencebased biomarker detection or electrochemical techniques have focused on improving AMI diagnosis accuracy and speed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 To our knowledge, there were only a few microfluidic devices developed for cTnI SERS detection, for example the use of plasmonic nanostrip microcone arrays has shown promising results. 24 Additionally, AuNPs coupled with magnetic beads were successfully implemented as signal transducers for LSPR detection. 25 Furthermore, the first approaches to exploit the heat generated by gold nanoparticles for biomedical applications emerged in the early 2000s, 26,27 thus becoming the foundation of the rapidly growing and promising field called thermoplasmonics.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical diagnosis for AMI is conducted using electrocardiography (ECG), coronary angiography, and assessment of biomarker levels. In contrast to the low accuracy of ECG, with 57% of patients diagnosed correctly, and utilizing the contrast agent in coronary angiography, which made this method invasive and time-consuming, the cTnI blood biomarker has been established as an extremely specific and sensitive measurement for a precise assessment of the progression of AMI disease. As a result, a sensitive and simple method for detecting cTnI is extremely valuable for AMI patients’ early detection and critical treatment. Nowadays, the primary method for detecting cTnI is based on the antigen–antibody interaction as an immunosensor or DNA binding as an aptasensor. Despite their high sensitivity and selectivity, immunosensors have several limitations, including low stability at high temperatures, a long period of the immune reaction, high antibody production costs, and the difficulty of chemically modifying antibodies for biological detection. Target-binding aptamers with resistance to harsh conditions, ease of chemical synthesis, and high specific affinity for fast-capturing cTnI have been developed as alternatives to antibodies. , By using the systematic evolution of ligands by exponential enrichment (SELEX) technique, Ban and colleagues developed extremely sensitive and selective single-stranded DNA aptamers against cTnI . Studies revealed that compared to the anti-cTnI antibody, Tro4 and Tro6 aptamers exhibited superior binding abilities to cTnI, and their dissociation constants were lower than those of the anti-cTnI antibody .…”
Section: Introductionmentioning
confidence: 99%